Evaluating in vivo approaches for studying the roles of thymic DCs in T cell development in mice - Wang, Yi; Chong, Mark M. W. (Frontiers in Immunology, 2024)
T cells express an enormous repertoire of T cell receptors, enabling them to recognize any potential antigen. This large repertoire undergoes stringent selections in the thymus, where receptors that react to self- or non-danger-associated- antigens are purged. We know that thymic tolerance depends on signals and antigens presented by the thymic antigen presenting cells, but we still do not understand precisely how many of these cells actually contribute to tolerance. This is especially true for thymic dendritic cells (DC), which are composed of diverse subpopulations that are derived from different progenitors. Although the importance of thymic DCs has long been known, the functions of specific DC subsets have been difficult to untangle. There remains insufficient systematic characterization of the ontogeny and phenotype of thymic APCs in general. As a result, validated experimental models for studying thymic DCs are limited. Recent technological advancement, such as multi-omics analyses, has enabled new insights into thymic DC biology. These recent findings indicate a need to re-evaluate the current tools used to study the function of these cells within the thymus. This review will discuss how thymic DC subpopulations can be defined, the models that have been used to assess functions in the thymus, and models developed for other settings that can be potentially used for studying thymic DCs.